Some maximum principles for solutions of a class of partial differential equations in Ω⊂ℝn - Mohammad Mujalli Al-Mahameed (International Journal of Mathematics and Mathematical Sciences)
We find maximum principles for solutions of semilinear elliptic partial differential equations of the forms: (1) Δ2u+αf(u)=0, α∈ℝ+ and (2) ΔΔu+α(Δu)k+gu=0, α≤0 in some region Ω⊂ℝn.